2017
DOI: 10.1016/j.prevetmed.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Associations between animal welfare indicators and Campylobacter spp. in broiler chickens under commercial settings: A case study

Abstract: Few studies have previously investigated how poor animal welfare might be associated with infection of zoonotic pathogens in humans. This paper assesses the predictive value of the presence of Campylobacter spp. in broiler chicken flocks when animal-based measures related to footpad dermatitis, hock burns, body lesions and arthritis are identified under commercial conditions (high density). The study population included 32 flocks analysed on farm and at slaughter, slaughtered between April and August 2008 in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The lower resistance levels contributed to higher bacterial counts and prevalence of E. coli and Salmonella in this group. These results were supported by those recorded by Alpigiani et al (2017) who stated that poor microclimatic conditions in broiler's houses contributed a higher litter humidity that acts as good media for enhancing the growth and multipli-cation of many pathogenic microorganisms as Salmonella and Campylobacter. Oakley et al (2018) also reported that alternations in macro and microclimatic conditions contributed to a stress factor and enhance pathogenic intestinal microorganisms and negatively influence performance.…”
Section: Discussionsupporting
confidence: 75%
“…The lower resistance levels contributed to higher bacterial counts and prevalence of E. coli and Salmonella in this group. These results were supported by those recorded by Alpigiani et al (2017) who stated that poor microclimatic conditions in broiler's houses contributed a higher litter humidity that acts as good media for enhancing the growth and multipli-cation of many pathogenic microorganisms as Salmonella and Campylobacter. Oakley et al (2018) also reported that alternations in macro and microclimatic conditions contributed to a stress factor and enhance pathogenic intestinal microorganisms and negatively influence performance.…”
Section: Discussionsupporting
confidence: 75%
“…Carcasses can be contaminated by manipulation, reflecting the hygienic level of the slaughterhouse and the animals' health status and farming conditions [24]. It has been shown that good farming conditions and the respect of animal welfare are clearly correlated with a lower rate of animal disease and of bacterial microorganisms at the gut level (i.e., Salmonella and Campylobacter) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some welfare measures in the past have been observed to correlate with changes in the gut microbiota and immune response of birds, such as stocking density (Gomes et al, 2014;Guardia et al, 2011), food withdrawal, and heat stress (Burkholder et al, 2008). More directly, lesions on the footpad and arthritis have been shown to be strong predictors of Campylobacter prevalence (Alpigiani et al, 2017), further supporting findings that flock movement patterns and behaviour can also accurately predict Campylobacter prevalence (Colles et al, 2016). Our own previous mathematical modelling studies have highlighted the potential for stocking density (Rawson et al, 2019) to impact the population dynamics of Campylobacter within a flock, and have also shown that the colonization status of an entire flock is greatly impacted by the • Company -A two-factor categorical variable, depicting whether the flock is overseen by company "1" or "2".…”
Section: Introductionmentioning
confidence: 84%